TINJAUAN PENILAIAN KINERJA KARYAWAN SEBAGAI DASAR PROMOSI JABATAN PADA PT. KERETA API INDONESIA (PERSERO) DIVISI REGIONAL III SUMATERA SELATAN - Roswaty Roswaty; Ikhwan Fauzan; Mohammad Kurniawan D.P (Jurnal Ilmiah Ekonomi Global Masa Kini)
This study aims to determine the effect of Achievement Employee Campaign Against Occupation In PT.Kereta Api Indonesia (Persero) Regional Division III South Sumatra .Penelitian have used a sample of 67 respondents and data collection using interviews, and assisted Statitical program for Product and Service Solution (SPSS) version 22 with computerized data analysis methods. Sampling using stratified random sampling method is sampling with regard strata (levels) in the population. Discussion of results of research using simple linear regression analysis to determine the effect Achievement Employee Campaign Against Occupation In PT.Kereta Api Indonesia (Persero) Regional Division III South Sumatra .Technique data collection is done through questionnaires or the distribution of questionnaires and interviews with respondents who selected .By simple regression test results indicate that there are influence employee performance against promotion on PT.Kereta Api Indonesia (Persero) Regional Division III South Sumatra amounting to 83.1 per cent and the remaining 16.9% is influenced by other variables not examined in this research. Key word : Employee Job Performance, Job Promotion